Sposoby zdobywania pożywienia i gospodarka ludności kultury pomorskiej na terenie Pojezierza Kaszubskiego i Starogardzkiego - Fudziński, Piotr (Zeszyty Wiejskie, 2011)
The article presents informations about the economy and the ways of pro ducing food in the early iron age (VI–IV b.C.) at the area of the Kaszubskie and Starogardzkie lake districts. The economy of the Pomeranian culture at this area was complicated. Due to the lack of knowledge about the settlements of this people our information are not full. The agriculture was depending on barley, wheat, rye and also millet and pea. Fields were being extensively used until the day they were impoverished, and then left for several years. Theoretically the early iron age agriculture was satisfying 2/3 demand for food. People were breeding cows and also pigs and sheep/goats. The hunting strategy was to follow sort of animals not for meat but also for horns (deer) and furs (beavers). The consumption of foxes and even squirrels can be included. Fishing (especially in springs) was also important – with fishes like breams, roaches and sanders. The type of economy developed in the early iron age was strongly depend ing on weather conditions. Droughts and on the other hands wet years could cause drop of clops and famine as result.